1991
DOI: 10.1007/bf00587636
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic autonomic neuropathy after pancreas and kidney transplantation

Abstract: Summary. We have evaluated the effect of successful pancreatic and kidney transplantation on autonomic neuropathy in nine Type 1 (insulin-dependent) diabetic subjects. Cardiovascular reflex tests were performed before and at 6-24 months after transplantation. A control group of ten Type I diabetic patients after kidney grafting only was examined at the same time periods. For base-line comparisons results of the tests in ten healthy subjects were used. Advanced autonomic neuropathy was present in both groups of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1996
1996
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…Conflicting results have been reported from renal and pancreatic-transplanted diabetic patients [21][22][23][24], however, improvement has been found after a follow-up period of 4ϩ years [22,23] therefore the follow-up of 17 months in the present investigation may be too short.…”
Section: Discussionmentioning
confidence: 63%
“…Conflicting results have been reported from renal and pancreatic-transplanted diabetic patients [21][22][23][24], however, improvement has been found after a follow-up period of 4ϩ years [22,23] therefore the follow-up of 17 months in the present investigation may be too short.…”
Section: Discussionmentioning
confidence: 63%
“…Solders et al [56] found an ameliorated R-R variability 4 years after transplantation, but this was true both for kidney/pancreas and renal graft recipients. The other studies [54,[57][58][59] could not demonstrate any significant change in beat-to-beat variation.…”
Section: Autonomic Neuropathymentioning
confidence: 70%
“…In chronic uremia, a study of our group failed to demonstrate a closely parallel involvement of somatic and autonomic functions [10]. Moreover, despite a clear improvement of somatic polyneuropathy, no significant change of autonomic dysfunction was found 6 and 12 months after renal transplantation, as well as up to 4 years after combined kidney-pancreas transplantation [20][21][22][23]. More recently, two different studies performed in diabetes demonstrated a divergent development of autonomic and peripheral somatic neuropathies, suggesting different pathophysiological processes [8,9].…”
Section: Discussionmentioning
confidence: 97%